2016
DOI: 10.5860/crl.77.6.682
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Assessment Tool for Quantitative Evaluation of Science Literature Search Performance: Application to First-Year and Senior Undergraduate Biology Majors

Abstract: Expertise in searching and evaluating scientific literature is a requisite skill of trained scientists and science students, yet information literacy instruction varies greatly among institutions and programs. To ensure that science students acquire information literacy skills, robust methods of assessment are needed. Here, we describe a novel tool for longitudinal, crossover assessment of literature-searching skills in science students and apply it to a cross-sectional assessment of literature-searching perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…While students in this study saw the value of giving credit, they had mixed feelings about citation styles and the process of citing accurately. Other researchers support this finding of increasing awareness but lack of specific skills regarding citation (Blank et al 2016). Citation is, therefore, a logical topic to include in librarian-led instruction.…”
Section: Information Has Valuementioning
confidence: 82%
See 1 more Smart Citation
“…While students in this study saw the value of giving credit, they had mixed feelings about citation styles and the process of citing accurately. Other researchers support this finding of increasing awareness but lack of specific skills regarding citation (Blank et al 2016). Citation is, therefore, a logical topic to include in librarian-led instruction.…”
Section: Information Has Valuementioning
confidence: 82%
“…Molteni and Chan (2015) found that upper-level health sciences students were over-confident in their abilities to complete research tasks. Blank et al (2016) developed an assessment tool to compare IL skills of first-year and senior biology students and found that seniors had stronger skills in searching peer-reviewed literature, citing articles correctly, and answering other questions about scientific literature correctly. They found that students with senior-level standing were more likely to find "relevant, peer-reviewed journal articles, provide appropriate citations, and provide correct answers to other questions about scientific literature," and first-year students and seniors also indicated different levels of training with such skills.…”
Section: Literature Reviewmentioning
confidence: 99%